Innovation in Decision-making Models Applied by Enterprises: Determinants of Organisational Innovation - Beata Skowron-Grabowska (Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie)
Objective: The paper addresses innovation as a vital issue in management. The meaning of innovation is analysed in knowledge management and business strategy. The intention of the article is to present the innovation issue from the model perspective and to illustrate the mentioned matters based on research results.